1969
DOI: 10.1210/endo-85-1-133
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for Ovine Luteinizing Hormone. Secretion of Luteinizing Hormone During Estrus and Following Estrogen Administration in the Sheep

Abstract: A solid-phase radioimmunoassay for ovine luteinizing hormone (LH) has been developed, utilizing antibody-coated polystyrene tubes for incubation of the assay and counting of the bound tracer. Tubes were coated with equine antiserum to bovine LH (Snook), and purified ovine LH (Papkoff) was used for iodination with 126 I and assay standards. The procedure is simple and rapid, being completely performed in the assay tubes and giving results after a period of 48 hr. Basal levels of plasma LH were 2.9 ±0.9 ng/ml in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
96
1
1

Year Published

1970
1970
1981
1981

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(111 citation statements)
references
References 17 publications
(19 reference statements)
13
96
1
1
Order By: Relevance
“…All plasma samples which were collected in these experiments were assayed for LH by using the solid-phase radioimmunoassay described by Goding et al (1969), in which a purified LH preparation with a biological potency of 2 x NIH-LH-Sl (Papkoff et al 1965) was used. The antiserum used in the assay was an anti-ovine LH serum which was provided by Dr W. Hansel, Cornell University, New York State.…”
Section: Hormonal Assaysmentioning
confidence: 99%
“…All plasma samples which were collected in these experiments were assayed for LH by using the solid-phase radioimmunoassay described by Goding et al (1969), in which a purified LH preparation with a biological potency of 2 x NIH-LH-Sl (Papkoff et al 1965) was used. The antiserum used in the assay was an anti-ovine LH serum which was provided by Dr W. Hansel, Cornell University, New York State.…”
Section: Hormonal Assaysmentioning
confidence: 99%
“…Plasma LH levels in experiments 1-4 were measured by a solid-phase radioimmunoassay (Goding et al 1969) and in experiment 4 by a double antibody method using the same antiserum, raised in a horse against bovine LH (Snook 1968) and used at a final dilution of 1 in 10 6 • The double antibody method used a goat anti-horse serum raised by Dr T. Stelmasiak, Department of Agriculture, Vic., as a source of second antibody (final dilution 1 in 250). Assay procedure was similar to that described by Lee et al (1976).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…For example, Findlay et al (1973) have reported that when infertile ewes which had previously grazed oestrogenic clover were ovariectomized, they were less likely to show elevated plasma LH levels, i.e. positive feedback (Goding et al 1969), in response to oestradiol-17f1 (E 2 ) treatment than were normal ovariectomized ewes. This reduced responsiveness of the hypothalamo-pituitary axis to E2 could be related to changes in the number or affinity of cytoplasmic Ez receptors in the pituitary gland, or both (Tang and Adams 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral plasma levels and anterior pituitary content of LH and FSH were determined by the radioimmunoassays reported by Goding et al (1969) and Salarnonsen et al (1973). Pituitaries were homogenized in O· 01M phosphate buffer (pH 7·4) and diluted 3 x 10 3 times prior to assay.…”
Section: Hormone Assay Proceduresmentioning
confidence: 99%